GAMBAR CADAS KALIMANTAN TIMUR: SATU BUKTI SENI LUKIS KUTAI PURBA - Gunadi Kasnowihardjo (BRIN, 2008)
Art including painting is an element of culture. Therefore art also becomes an object of archaeological research. Rock art paintings found in prehistoric caves in Kutai Timur regency of East Kalimantan Province are categorized as art paintings of prehistoric era. In prehistoric archaeology, arts and religion were difficult to be separated. Rock art paintings should be analized by religion approach and arts approach as well.